Kuat Tekan Mortar Berbasis Serat Kelapa dan Limbah Kaca - Nalia, Fira; Rahmawati, Cut; Silviana, Mery (Jurnal Teknik Sipil Unaya, 2025)
This study aims to determine the effect of using glass waste and coconut fiber in mortar with various percentages, namely 0%, 5%, 10%, 15% glass powder and 0%, 1%, 2% coconut fiber with a total of 21 test objects, then testing was carried out after the test objects were 28 days old. The test results showed that the addition of coconut fiber and glass powder with a percentage of coconut fiber of 1% and glass powder of 5%, 10%, 15% in the mortar mixture increased the compressive strength by 17.65 MPa, 18.57 MPa, and 25.36 MPa. However, the addition of coconut fiber by 2% and glass powder 5%, 10%, 15% decreased the compressive strength to 16.97 Mpa, 16.68 Mpa, and 16.44 Mpa.